J Child Adult Vaccines Immunol 2019
DOI: 10.29328/journal.jcavi.1001003
|View full text |Cite
|
Sign up to set email alerts
|

Demographic survey and management outcome of Post-Neonatal Tetanus at the Ekiti state university teaching hospital, Ado Ekiti

Abstract: Background: Tetanus continues to threaten the survival of children in spite of it being a vaccine preventable disease. The objective of this study was to determine the prevalence of post-neonatal tetanus, review the vaccination of affected children, complications encountered and the outcome among affected children in a tertiary health institution in southwestern Nigeria. Methods: The study was a retrospective study. Case notes of children outside neonatal life admitted to the Paediatric ward with clinical diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The parents/caregivers of all the children with PNT in this study were from low socio-economic class as also reported by Ajite et al in Ekiti. [32] In other studies in Nigeria, majority of children treated for PNT were also from families with low socio-economic class. [27,31] The exact reason for this observation is not known, it has however been attributed to the fact that these children are more exposed to poor hygienic environments, have risky behaviours like playing barefoot and unsupervised outdoor play.…”
Section: Discussionmentioning
confidence: 97%
“…The parents/caregivers of all the children with PNT in this study were from low socio-economic class as also reported by Ajite et al in Ekiti. [32] In other studies in Nigeria, majority of children treated for PNT were also from families with low socio-economic class. [27,31] The exact reason for this observation is not known, it has however been attributed to the fact that these children are more exposed to poor hygienic environments, have risky behaviours like playing barefoot and unsupervised outdoor play.…”
Section: Discussionmentioning
confidence: 97%